Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.2217/fon-2017-0302
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab in advanced lung cancer: state of the art

Abstract: Despite recent advances in metastatic lung cancer treatment with the advent of immune checkpoint inhibitors and molecules targeting addictive genomic abnormalities, prognosis of most of the patients remains unfavorable. Combination approaches with older drugs, such as bevacizumab, should be thus envisioned. Bevacizumab is a monoclonal anti-VEGF antibody, approved by the US FDA and the EMA in first-line and maintenance settings of advanced nonsquamous non-small-cell lung cancer (NSCLC) treatment, in association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 103 publications
0
39
0
Order By: Relevance
“…Therefore, antiangiogenesis therapy plays an important role in oncotherapy. However, bevacizumab was approved only for nonsquamous NSCLC . Nintedanib prolonged overall survival (OS) only in patients with ACC .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, antiangiogenesis therapy plays an important role in oncotherapy. However, bevacizumab was approved only for nonsquamous NSCLC . Nintedanib prolonged overall survival (OS) only in patients with ACC .…”
Section: Introductionmentioning
confidence: 99%
“…This study revealed promising antitumor synergy and a high MPE control rate after treatment with bevacizumab plus chemotherapy. One of the probable mechanisms of the synergistic effect of bevacizumab plus chemotherapy is based on the theory of bevacizumab‐induced tumor vascular normalization, which is considered to decrease tumoral interstitial hypertension, subsequently enhancing efficacious delivery and the uptake of drugs . A study from China showed that the use of paclitaxel and bevacizumab enhances the treatment effect in NSCLC patients with MPE .…”
Section: Discussionmentioning
confidence: 99%
“…One of the probable mechanisms of the synergistic effect of bevacizumab plus chemotherapy is based on the theory of bevacizumab-induced tumor vascular normalization, which is considered to decrease tumoral interstitial hypertension, subsequently enhancing efficacious delivery and the uptake of drugs. 20 A study from China showed that the use of paclitaxel and bevacizumab enhances the treatment effect in NSCLC patients with MPE. 17 Qi et al reported that T1/2a (hour) of paclitaxel in pleural fluid samples were 4.58 AE 0.45 and 0.83 AE 0.05 in paclitaxel and paclitaxel/bevacizumab-treated patients, respectively (P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Bevacizumab is another monoclonal antibody (humanized) that blocks the VEGF and interferes with its binding to its receptors. Thus, it inhibits angiogenesis, which is an essential process for the development of new blood vessels to supply cancer cells with oxygen and nutrients [120]. Bevacizumab showed productive anticancer activities against colorectal, kidney, lung, breast and head and neck cancers [111].…”
Section: Immune Therapies: Bevacizumab As An Examplementioning
confidence: 99%